Sport-Specific Skills Differentiate Performance Levels Better Than Anthropometric or Physiological Factors in Beach Handball. Issue 4 (2nd October 2022) - Lemos, Luís; Nevill, Alan; Duncan, Michael J.; De Oliveira, Vinícius C.; Pino-Ortega, José; Santos, Amilton; Martins, Clarice; Nakamura, Fábio
ABSTRACT: Beach handball is characterized by high- and low-intensity efforts on an unstable surface. Players are expected to display high levels of physical performance on sand, though there are no data concerning success in elite players. Purpose : This study aimed to address anthropometric, fitness, and sport-specific skills components in beach handball, by comparing elite national team beach handball players (world champions) to sub-elite players (playing at a regular club). Method : A total of 91 senior players (more than 21 years old) of both genders (19 world champions) were assessed for anthropometry, 5-m acceleration, 15-m sprint, handgrip strength, horizontal jump, and three specific sport-specific skills (ball velocities in standing, inflight and spin throwing) at a beach court. Anthropometric, physiological, and sport-specific skill test variables were analyzed as a multiple dependent variable using a multivariate analysis of variance (MANOVA) with sex and level (elite vs sub-elite) as the fixed factors. SPSS (25.0) was used, significance was assumed at p < .05. Results : The results highlighted that for male and female athletes, horizontal jump, 6-m standing, spin, and inflight throwing discriminated between elite and sub-elite groups ( p < .001). Conclusion : The study suggests that the factors which differentiate between elite and sub-elite performers in beach handball are horizontal jump and technical ability via the performance of specific throwing skills, rather than anthropometric or any other physical variables, irrespective of sex. These findings highlight some of the relevant physical capacities and skills that need to be developed over the years of preparation of top-level beach handball players.